2018
DOI: 10.1038/s41598-018-22232-w
|View full text |Cite
|
Sign up to set email alerts
|

Association of clinicopathological features and prognosis of TERT alterations in phyllodes tumor of breast

Abstract: Phyllodes tumor (PT) of the breast is a rare but clinically important fibroepithelial tumor with potential risks of recurrence and metastasis. Recent studies identified recurrent TERT promoter mutations in PTs. However, the clinical significance of this alteration has not been fully examined. Two hundred and seven PTs from two intuitions were included. All cases were subjected to immunohistochemical analysis for TERT expression. Analysis of TERT promoter mutations was further performed by Sanger sequencing tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…In contrast, phyllodes tumours (PTs) are much less often diagnosed, and while they usually affect older women, younger women, particularly Asians, can be afflicted with PTs 1. Tsang et al have described differences in TERT promoter mutation patterns of PTs in Asians compared with Caucasians and have suggested that this may reflect the differences in PT pathogenesis among different ethnicities 2. Our recent work on an international cohort of fibroepithelial lesions, to be further elaborated on in this paper, has also revealed a higher frequency of KMT2D mutations in non-Asian PTs compared with Asian PTs 3.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…In contrast, phyllodes tumours (PTs) are much less often diagnosed, and while they usually affect older women, younger women, particularly Asians, can be afflicted with PTs 1. Tsang et al have described differences in TERT promoter mutation patterns of PTs in Asians compared with Caucasians and have suggested that this may reflect the differences in PT pathogenesis among different ethnicities 2. Our recent work on an international cohort of fibroepithelial lesions, to be further elaborated on in this paper, has also revealed a higher frequency of KMT2D mutations in non-Asian PTs compared with Asian PTs 3.…”
Section: Introductionsupporting
confidence: 52%
“…TERT promoter mutations were found at the highest frequency in borderline PTs, compared with malignant PTs, and the least in benign PTs 2 3 26. Additionally, while stromal TERT protein expression was high in both borderline and malignant PTs, it was correlated only to TERT promoter mutations in borderline PTs, suggesting that other molecular aberrations could exist in malignant PTs to increase TERT expression 2.…”
Section: ​Tertmentioning
confidence: 92%
See 2 more Smart Citations
“…We noted that 18 out of 303 (6%) FAs displayed TERT promoter –124C>T (chr5:1,295,228 C>T) and –146C>T (chr5:1,295,250 C>T) mutations (see supplementary material, Table S4), while Yoshida et al discovered that four out of their 58 (7%) FAs were positive for –124C>T mutations, in contrast to none being observed in three other cohorts . PTs showed a significantly higher rate of 41% (200 out of 493 cases), especially in the borderline grade (61%), as similarly recorded by both Yoshida et al and Tsang et al . Interestingly, FELs with mutant MED12 were more likely to have TERT promoter mutation concurrently than those with wild‐type MED12 (37% versus 17%, p < 0.001), in agreement with the findings by Yoshida et al and Piscuoglio et al .…”
Section: Discussionmentioning
confidence: 77%